2016
DOI: 10.1063/1.4948264
|View full text |Cite
|
Sign up to set email alerts
|

Electric field induced lattice strain in pseudocubic Bi(Mg1/2Ti1/2)O3-modified BaTiO3-BiFeO3 piezoelectric ceramics

Abstract: Contributions to the piezoelectric response in pseudocubic 0.3BaTiO3-0.1Bi(Mg1/2Ti1/2)O3-0.6BiFeO3 ceramics were investigated by synchrotron X-ray diffraction under electric fields. All of the lattice strain determined from the 110, 111, and 200 pseudocubic diffraction peaks showed similar lattice strain hysteresis that was comparable to the bulk butterfly-like strain curve. It was suggested that the hysteresis of the lattice strain and the lack of anisotropy were related to the complex domain structure and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The peak shift behaviors observed under the electric fields were similar to those of the 0.86BNT0.14KNN and 0.3BaTiO 3 0.1(Mg 1/2 Ti 1/2 )0.6BiFeO 3 lead-free piezoelectric materials. 24), 25) It is worthy to mention that the shape of the diffraction peaks observed with and without the application of the electric fields, were exactly the same; single peak. Single peak for the zero electric field XRD patterns were reported to separate with the application of electric fields in BNT BT and BNTBTKNN ceramics.…”
Section: Figure 2 Shows Ferroelectric and Electric-field-inducedmentioning
confidence: 72%
“…The peak shift behaviors observed under the electric fields were similar to those of the 0.86BNT0.14KNN and 0.3BaTiO 3 0.1(Mg 1/2 Ti 1/2 )0.6BiFeO 3 lead-free piezoelectric materials. 24), 25) It is worthy to mention that the shape of the diffraction peaks observed with and without the application of the electric fields, were exactly the same; single peak. Single peak for the zero electric field XRD patterns were reported to separate with the application of electric fields in BNT BT and BNTBTKNN ceramics.…”
Section: Figure 2 Shows Ferroelectric and Electric-field-inducedmentioning
confidence: 72%
“…In such a scenario, the cubic symmetry can theoretically change to a lower symmetry, as exhibited by the splitting of specific XRD peaks. Synchrotron radiation powder XRD (SXRD) experiments have confirmed that an electric-field-induced phase transition does not occur in 0.3BT-0.1BMT-0.6BF ceramics 27 . Nevertheless, 0.3BT-0.1BMT-0.6BF ceramics with a pseudocubic symmetry distinctly exhibits the most substantial piezoelectric and ferroelectric responses at room temperature among all BT-BMT-BF systems.…”
mentioning
confidence: 99%
“…In the case of 0.3BT-0.1BMT-0.6BF ceramics, all the single-diffraction peaks shift significantly under an applied electric field without peak splitting, which suggests that the dimensions of the crystal lattice can easily change, irrespective of the crystallographic direction in which the electric field is applied. The intrinsic contributions originating purely from the crystal lattice seem to play important roles in the exhibition of the large piezoelectric response in 0.3BT-0.1BMT-0.6BF ceramics; this is because particular domain structures cannot be expected owing to their pseudocubic symmetry 27 . In contrast, in both the rhombohedral and tetragonal structures of PZT-based ceramics, the positions of the diffraction peaks related to the polarization directions, i.e., (111) and (002) diffraction peaks, respectively, are almost unchanged under an applied electric field 28,29 .…”
mentioning
confidence: 99%
“…These authors believed the high strain mainly came from the enhancement of domain wall density and mobility under the applied electric field. However, Wada et al 100,101 investigated the effect of electric field on the phase structure and piezoelectric response for both pure BF-BT and Bi(Mg 1=2 Ti 1=2 ÞO 3 (BMT) doped BF-BT by in-situ synchrotron radiation X-ray diffraction (SR-XRD). No peak splitting was observed in the diffraction peaks ( Fig.…”
mentioning
confidence: 99%
“…The absence of T phase in the vicinity of optimized composition, suggests that the ferroelectric phase is most likely R and thus peak splitting is difficult to observe in in-situ studies. 100,101 This model however, requires further verification through in-situ studies that focus on determining the structure of the field induced state. Structural refinements however, are complicated by the core-shell microstructure often reported in undoped and doped compositions, and we recommend that future investigations are carried out on chemically homogeneous samples (by BSE images) such as those described by Murakami et al 56,57 A comparison of d 33 versus T C =T m , d à 33 versus T C =T m and S max versus d à 33 for lead-based and lead-free piezoelectric ceramics is plotted in Fig.…”
mentioning
confidence: 99%